Systematic Review of Pain Severity and Opioid Craving in Chronic Pain and Opioid Use Disorder. Issue 2 (17th September 2019) - MacLean, R Ross; Spinola, Suzanne; Manhapra, Ajay; Sofuoglu, Mehmet
Abstract: Objective: To evaluate measurement and associations between pain severity and opioid craving in individuals with chronic pain on long-term opioid therapy and/or with opioid use disorder. Study Design: . Systematic review of randomized controlled trials and observational studies. Methods: . The PubMed, EMBASE, and PsycINFO databases were searched in October 2018. Eligible studies evaluated pain severity and opioid craving in individuals with chronic pain on long-term opioid therapy and/or with opioid use disorder. Two reviewers independently screened eligible studies, assessed risk of bias, and extracted data. Results: Of 625 studies, 16 fulfilled the inclusion/exclusion criteria of this review and were grouped by diagnostic focus (i.e., chronic pain on long-term opioid therapy, opioid use disorder, or both). Methods of assessment varied considerably across studies, especially with respect to opioid craving in chronic pain populations. Mean levels of pain were at what is considered moderate to severe in individuals with chronic pain and/or opioid use disorder. There was a modest positive relationship between pain and opioid craving that was more pronounced in studies of individuals with opioid use disorder compared with those with chronic pain on long-term opioid therapy. Conclusions: Pain severity and opioid craving are likely related, but inconsistencies in measurement limit confidence. The overall quality of evidence is moderate, and careful consideration of how pain and craving are assessed in both chronic pain and opioid use disorder patients is warranted.